Undoing ableism teaching about disability in K-12 classrooms - Lalvani, Priya; Baglieri, Susan (New York, NY : Routledge, 2019)
Undoing Ableism is a sourcebook for teaching about disability and anti-ableism in K-12 classrooms. Conceptually grounded in disability studies, critical pedagogy, and social justice education, this book provides both a rationale as well as strategies for broad-based inquiries that allow students to examine social and cultural foundations of oppression, learn to disrupt ableism, and position themselves as agents of social change. Using an interactive style, the book provides tools teachers can use to facilitate authentic dialogues with students about constructed meanings of disability, the nature of belongingness, and the creation of inclusive communities.
OCLC-licensed vendor bibliographic record.
Keywords: EDUCATION / General; Discrimination against people with disabilities -- Prevention -- Study and teaching; Disabilities -- Study and teaching